2017
DOI: 10.1530/rep-16-0615
|View full text |Cite
|
Sign up to set email alerts
|

In vivo targets of human placental micro-vesicles vary with exposure time and pregnancy

Abstract: Throughout human gestation, the placenta extrudes vast quantities of extracellular vesicles (EVs) of different sizes into the maternal circulation. Although multinucleated macro-vesicles are known to become trapped in the maternal lungs and do not enter the peripheral circulation, the maternal organs and cells that smaller placental micro-vesicles interact with remain unknown. This study aimed to characterise the interaction between placental micro-vesicles and endothelial cells and to elucidate which organs p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 47 publications
4
47
2
Order By: Relevance
“…The syncytiotrophoblast is bathed in maternal blood and produces vast quantities of EVs in normal pregnancy. These EVs are extruded directly into the maternal blood and target specific maternal organs [5,6]. We have previously shown that EVs produced by the syncytiotrophoblast in normal pregnancies are tolerogenic to both immune and endothelial cells, but EVs from preeclamptic placentae are dangerous/toxic and activate endothelial cells [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The syncytiotrophoblast is bathed in maternal blood and produces vast quantities of EVs in normal pregnancy. These EVs are extruded directly into the maternal blood and target specific maternal organs [5,6]. We have previously shown that EVs produced by the syncytiotrophoblast in normal pregnancies are tolerogenic to both immune and endothelial cells, but EVs from preeclamptic placentae are dangerous/toxic and activate endothelial cells [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…If, following exposure to antiphospholipid antibodies, the syncytiotrophoblast is not functioning adequately because it is responding to endoplasmic reticulum stress, this may cause reduced nutrient/gas transfer across the placenta and lead to fetal growth restriction, one of the complications that occurs in women with Antiphospholipid antibody Syndrome [48]. In addition, the export of both micro-EVs and nano-EVs containing misfolded proteins may harm the maternal cells that take up these vesicles [5,49]. We have previously shown that EVs from placentae treated with antiphospholipid antibodies contain increased amounts of various danger signals including mitochondrial DNA [50] and HMGB1 [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the increased levels of Flt-1 on micro- and nano-vesicles from PE placentae, vesicle-associated Flt-1 accounted for less than 7% of the total sFlt-1 secreted by PE placentae. Nevertheless, EV-associated Flt-1 may still be an important contributor to the pathogenesis of preeclampsia because: (1) we have shown that increased numbers of micro- and nano-vesicles are extruded by PE placentae and (2) we have previously reported that different size fractions of EVs are targeted to specific maternal organs such as the kidneys and liver, organs that are affected in preeclampsia (52, 54). Therefore, while increased levels of free sFlt-1 may mediate global endothelial cell dysfunction by sequestering circulating VEGF, vesicle-associated Flt-1 may be concentrated in specific organs such that even a low circulating level of vesicle-associated Flt-1 may have a large biological significance by causing organ-specific endothelial cell damage, such as glomerular endotheliosis which is commonly reported in women with preeclampsia (3, 6).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the bioactivity of exosomes is greatest during first trimester and gradually decline with increasing gestational age . Tong et al demonstrate that different size fractions of placental EVs can rapidly interact with ECs and localize to different organs in vivo, which supports the notion that placental EVs are likely to have effects on endothelial functions. Placental nano‐vesicles interact with ECs rapidly in vitro through a combination of mechanisms including phagocytosis, endocytosis and cell surface binding.…”
Section: Evs In Normal Pregnancymentioning
confidence: 92%